Sr and Pb isotopic investigation of mammal introductions: Pre-Columbian zoogeographic records from the Lesser Antilles, West Indies. (May 2016) - Giovas, Christina M.; Kamenov, George D.; Fitzpatrick, Scott M.; Krigbaum, John
Abstract: Recent efforts to reconstruct the anthropogenic paleozoogeography of introduced Neotropical mammals in the West Indies provide new analytical foundations for evaluating island and continental human interaction, exchange, colonization, and animal management. Key questions in these investigations concern the timing, source, population viability, and environmental impact of continental faunal translocations in the pre-Columbian insular Caribbean. To investigate these issues we analyzed 87 Sr/ 86 Sr, 206 Pb/ 204 Pb, 207 Pb/ 204 Pb, and 208 Pb/ 204 Pb isotope ratios from environmental samples and agouti ( Dasyprocta sp.) and opossum ( Didelphis cf. marsupialis ) remains from Ceramic Age (500 BC – AD 1500) archaeological deposits on the islands of Nevis, Carriacou, and Mustique in the Lesser Antilles. This study was undertaken to assess the suitability of agouti and opossum tooth enamel for isotopic analysis, characterize local bioavailable Sr and Pb isotope ratios, and distinguish possible local and non-local agouti and opossum individuals. We demonstrate large intra-island variability in bioavailable Sr across multiple islands giving rise to potential equifinality in identifying taxa of non-local origin. We argue, consequently, for the necessity of comprehensive environmental sampling at the island scale to better define the range and mean of bioavailable Sr for a given locale. Our results further show that Pb isotope analysis of sampled taxa is problematized to varying degrees by modern anthropogenic lead contamination, even for well-preserved 'clean' tooth enamel from intact archaeological specimens and raise questions about the utility of this method for evaluating past animal translocations and the use of small mammals for establishing local bioavailable Pb. Despite these results, Sr data are sound and, in combination with vetted Pb ratios, indicate that agouti and opossum were established as living populations on Carriacou and Nevis as early as ca. AD 600/800, and possibly earlier. These results establish baseline data for evaluating exchange networks involving living animals or their parts, potential captive management of agouti and opossum, and the ecological impact of exotic species during the Pre-Columbian era in the West Indies. Highlights: Sr and Pb isotope analysis of tooth enamel from prehistorically introduced agouti and opossum. Environmental samples provide bioavailable Sr and Pb ratios for the Lesser Antilles. Agouti and opossum likely established as viable populations on Nevis and Carriacou. Modern anthropogenic Pb contamination observed in well-preserved tooth enamel. Results inform paleomobility, invasion biology, and analytic reliability of Pb isotopes for small mammals.